2016
DOI: 10.23953/cloud.ijarsg.48
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Urban Heat Islands in Cairo City, Egypt using Time Series of Landsat Satellite Images

Abstract: Global warming has obtained more attention because of increasing global mean surface temperature since the late 19th century. Urbanization is considered an important contributor to global warming in big cities. Cairo is one of the heavily populated cities in the world, which has rapid urbanization that resulted in remarkable temperature variation compared to the rural surrounding areas. This phenomenon is known as "Urban Heat Islands" (UHIs) that influence both local and regional climate, environment, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 49 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…The results are in accordance with the consensus that there was higher LST in urban areas compared to the surrounding areas. This agrees with the finding from cities such as Cairo in Egypt, where there is little or no vegetation in urban areas (El-Magd et al, 2016). CoT is also known as the Jacaranda City a pseudonym that was derived from the Jacaranda trees in the streets together with other different indigenous and alien tree species.…”
Section: Land Surface Temperature (Lst)supporting
confidence: 88%
See 1 more Smart Citation
“…The results are in accordance with the consensus that there was higher LST in urban areas compared to the surrounding areas. This agrees with the finding from cities such as Cairo in Egypt, where there is little or no vegetation in urban areas (El-Magd et al, 2016). CoT is also known as the Jacaranda City a pseudonym that was derived from the Jacaranda trees in the streets together with other different indigenous and alien tree species.…”
Section: Land Surface Temperature (Lst)supporting
confidence: 88%
“…where N is the pixel normalised value of the LST, Ti is the LST of the i th pixel, Tmin is the minimum value of the LST and Tmax is the maximum LST. The normalised LST can be divided into five zones, which are strong heat islands zone (0.8-1.0), heat islands zone (0.6-0.8), normal zone (0.4-0.6), green islands zone (0.2-0.4) and strong green islands zone (0-0.2) (El-Magd et al, 2016;Xu et al, 2013).…”
Section: Normalising Brightness Temperaturementioning
confidence: 99%
“…In addition, in a study conducted by El-Metwally et al [35] on the impacts of aerosols on solar radiation transfer using AERONET data, it was concluded that the three dominant aerosol components in Egypt are (1) the highly absorbing aerosols produced by daily activities, (2) aerosols produced from burning agricultural wastes in the Nile delta region and (3) desert dust. Each of these aerosol components combine with human activities and lead to the occurrence of heat islands over Cairo, Abou, El-Magd, et al [39]. The purpose of this research is to intensively examine for the first time the temporal and spatial variations of atmospheric aerosols over Egypt from 2012 to 2018 using both MODIS Terra and AERONET data.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Various studies have used satellite data to observe atmospheric aerosol characteristics worldwide [4,20,21,[29][30][31][32][33][34]. In Egypt, research studies have been carried out on atmospheric aerosols with a particular focus on Cairo and the Nile delta region [33,[35][36][37][38][39][40][41][42] due to their high pollution load. Shokr [36] discussed aerosol characteristics over five Egyptian cities using MODIS Aqua aerosol data.…”
Section: Introductionmentioning
confidence: 99%
“…In summer 2012, land surface temperature (LST) varied from 27°C to 61°C [7]. The UHI intensity index in Cairo has five dominant levels, with least intensity in vegetated areas/water bodies, while highest in scattered bare land areas and industrial zones [9]. Thus, the above observations make it a necessity to develop means to determine the hot spots in Cairo Governorate, to prioritize and propose strategies for high temperatures mitigation.…”
Section: Objectivesmentioning
confidence: 99%